2018
DOI: 10.1093/ofid/ofy249
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Related Staphylococcus aureus Bacteremia and Septic Thrombosis: The Role of Anticoagulation Therapy and Duration of Intravenous Antibiotic Therapy

Abstract: BackgroundCatheter-related septic thrombosis is suspected in patients with persistent central line–associated bloodstream infection (CLABSI) after 72 hours of appropriate antimicrobial therapy. The clinical diagnosis and management of this entity can be challenging as limited data are available. We retrospectively studied the clinical characteristics of patients with Staphylococcus aureus catheter-related septic thrombosis and the outcomes related to different management strategies.MethodsThis retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…The duration of treatment of suppurative thrombophlebitis is based on expert opinions. A recent retrospective study on patients with S. aureus suppurative thrombophlebitis showed that a duration of antibiotic therapy shorter than 28 days and the absence of anticoagulant therapy were associated with higher rates of treatment failure [ 172 ].…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…The duration of treatment of suppurative thrombophlebitis is based on expert opinions. A recent retrospective study on patients with S. aureus suppurative thrombophlebitis showed that a duration of antibiotic therapy shorter than 28 days and the absence of anticoagulant therapy were associated with higher rates of treatment failure [ 172 ].…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…However, in patients without persistent bacteremia, determination of whether a thrombus is actively infected is difficult, and guidance is lacking. Regardless of duration of bacteremia, thrombosis in this setting has been associated with poor outcomes if treated with <28 days of antibiotic therapy [ 10 ]. The presence of thrombosis should therefore be considered when determining the treatment duration in SAB.…”
Section: Discussionmentioning
confidence: 99%
“…Septic thrombosis (ST) is a serious and potentially fatal condition defined by the presence of an endovascular thrombus in the setting of associated bacterial or fungal infection [1][2][3][4]. The cornerstones of ST treatment include prolonged and targeted antimicrobial therapy and anticoagulation [1,4,5]. Furthermore, in selected cases surgical debridement may also be required [6][7][8].…”
Section: Introductionmentioning
confidence: 99%